We want justice : Jamaica and the Caribbean Court of Justice - Ranklyn, Delano (Ian Randle Publishers KingstonJM, 2005)
Presents presentations by the main participants in the Jamaican parliamentary debates, views and opinions of members of local and Caribbean civil society surrounding the establishment of the Caribbean Court of Justice.